Marketing plans : how to prepare them, how to use them - McDonald, Malcolm; Wilson, Hugh, 1962- (Chichester, West Sussex, U.K. : Wiley, 2011)
"Marketing Plans, Seventh Edition presents a practical, no-nonsense style and approach that helps and encourages practicing managers with the difficult task of marketing planning. This helpful text illustrates the process of preparing a marketing plan, how to manage that process, and how to put the plan in action. The new edition has been thoroughly updated with contemporary thinking and includes new information on multi-channel integration and other new electronic routes to market. All case material and examples have also been revised."--
Understanding the Marketing Process -- The Marketing Planning Process: 1 The Main Steps -- The Marketing Planning Process: 2 Removing the Myths -- Completing the Marketing Audit: 1 The Customer and Market Audit -- Completing the Marketing Audit: 2 The Product Audit -- Setting Marketing Objectives and Strategies -- The Integrated Marketing Communications Plan -- The Sales Plan -- The Pricing Plan -- The Multichannel Plan: The Route to Market -- The Customer Relationship Management Plan -- Implementation Issues in Marketing Planning -- Measuring the Effectiveness of Marketing Planning -- A Step-by-Step Marketing Planning System.
Includes bibliographical references and index.
Print version record.
eBooks on EBSCOhost
Keywords: Marketing -- Management; Marketing -- Planning; Marketing -- Management; Marketing -- Planning; BUSINESS & ECONOMICS -- Green Business; Marketing -- Management; Marketing -- Planning; elektronické knihy; electronic books